Adverse effects of hysteroscopy, prevention and treatment: literature review - Baum, Marcin; Woźniak, Piotr; Stetkiewicz, Tomasz; Oszukowski, Przemysław (Menopause Review/Przegląd Menopauzalny, 2013)
Hysteroscopy has become a gold standard for diagnosis and treatment of many pathologies that affect uterine cavity and cervical channel. Unfortunately, like other invasive procedures, this technique is not free from adverse effects. One should mention uterine perforation, hemorrhage, infection, fluid overload, gas embolism and cervical laceration. The problem of dissemination of endometrial cancer cells into the peritoneal cavity during hysteroscopy and its influence on prognosis of patients is still unresolved. The aim of this article is to present the most important adverse effects of hysteroscopy, their etiology, and some ways of prevention and therapy.